PELEMAHAN RUPIAH: MANAJEMEN NILAI TUKAR INDONESIA DAN PELAJARAN DARI MASA LALU - Sonny Harry B Harmadi (Jurnal Keuangan dan Perbankan, 2016)
World ecomonic trend in 2008 has decreased significantly after growing rapidly for a decade (world economic growth up to 2007 was 5.2%). Global contraction happened because of United States and Europe performance decreasing. In 2008, this impact had spread to all around the world including Asia and especially Indonesia. This paper aims to consider Indonesia Experience in Exchange Rate Management policy. This paper con-cerned on pre-1990 period which was highlighted by the exchange value rezime and with all of the variations.